Analysis of the Impact of Green Banking, Inflation Rates, and Bad Loans on the Profit Growth of Banking Companies Listed on the IDX - Ni Luh De Erik Trisnawati; Desak Kadek Irma Wahyuni; Sarbaeni Sarbaeni (Yayasan Riset dan Pengembangan Intelektual, 2023)
The purpose of this study was to determine the effect of the implementation of green banking, inflation, and non-performing loans on profit growth. This study uses secondary data and time series on banking sector companies listed on the Indonesia Stock Exchange from 2019 to 2021. This research uses a quantitative. The population in this study are banking companies listed on the Indonesia Stock Exchange, totalling 12 companies. The data analysis technique in this study was descriptive statistical analysis, classical assumption test, multiple linear regression analysis, and hypothesis testing using the SPSS program for Windows version 25.0. Based on the testing and results of data analysis and discussion of data results (prove the hypothesis), it is concluded that green banking does not affect profit growth. The inflation rate has a negative and significant effect on profit growth. And bad credit has a positive and significant effect on profit growth.